85Kr Thickness Gauge Source in Measuring the Areal Density of Lithium Battery Electrodes - Yunfei BAI; Binbin LIANG; Yigang PENG; Zheng GE (Journal of Isotopes)
In order to meet the widespread application of 85Kr thickness gauge sources in the new energy lithium battery industry，an application study was conducted on the thickness gauge's use in measuring the coating areal density of lithium battery electrodes. The influence of the source window material，thickness，active area，and activity size on the beta ray output of different specifications of 85Kr thickness gauge was compared and analyzed. The quantitative calibration，temperature compensation calibration，position compensation calibration，and source activity decay compensation calibration of the 85Kr thickness gauge's beta ray absorption value in the actual production process of lithium battery electrodes were completed.The relationship curve between the areal density of the electrode and the beta ray absorption value was obtained，as well as the relationship between the surface density of the electrode and temperature，position，and source activity decay. The research results show that The 85Kr thickness gauge source with a thickness of 25 μm titanium window，a large bottom area and low height of the active zone，and a loading activity of 18.5 GBq has a large betaray output，and the repeatable measurement precision is 0.02%；The linear correlation between the attenuated absorption value of the beta ray after the transmission pole piece and the areal density is 0.999. Measuring the air temperature of the gap compensates for the effect of changes in air density on beta ray absorption. The position change of the pole piece distance detector is linearly related to the measured areal density，compensates for the measured areal density by measuring the position of electrodes. Correct I0 at least every 5 days to compensate for the deviation of the measurement system caused by the activity attenuation of the 85Kr thickness gauge source.The thickness gauge using 85Kr as the radiation source can meet the actual application needs of the super intelligent manufacturing line of lithium-ion batteries.